Digital Transformation In Financial Management - Saputra, Muhammad Fadli; Susena , Karona Cahya (Universitas Dehasen Bengkulu, 2025)
This study analyzes the impact of digital transformation on the financial management of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia in the digital economy era. MSMEs play an important role in the national economy, but face challenges such as low digital and financial literacy, limited access to technology, and uneven infrastructure. Digital transformation offers various opportunities, including operational efficiency, transparency of financial reports, and access to fintech-based financial services. However, risks such as data security and resistance to change are also concerns. Using a literature review method, this study identifies strategies that can be implemented to support the adoption of digital technology by MSMEs. The results show that digital literacy, government support, and the development of technological infrastructure are key elements in maximizing the benefits of digital transformation. This study provides practical contributions for MSME actors and policy makers to create an ecosystem that supports the sustainability and competitiveness of MSMEs in the digital era.